Improvement of alternaria leaf blotch and fruit spot of apple control through the management of primary inoculum - Cabrefiga, Jordi (2023)
Alternaria spp. is the causal agent of apple leaf blotch and fruit spot, diseases of recent appearance in Spain. The overwinter inoculum of Alternaria spp. is the source of primary infections in apple, thus the aim of this work was to optimize the control of infection through two environmentally friendly inoculum-management strategies, the removal of winter fallen leaves and the treatment of leaves with the biological agent Trichoderma asperellum to inhibit or prevent inoculum development in commercial orchards. The results of commercial orchard trials showed that leaf aspiration and application of T. asperellum on the ground have efficacy to reduce fruit spot between 50 and 80% and leaf blotch of between 30 and 40% depending on the year. The efficacies on the reduction of leaf blotch were slightly lower than of fruit spot. Disease reduction has been related to a reduction of total spores released during the season. Results of dynamics of spore release indicate that factors influencing spore release were rainfall and temperature. In conclusion, the use of environmentally friendly strategies combined with standard fungicides, and with monitoring environmental conditions, might allow a reduction in the number of phytosanitary applications, thus achieving the goal of reducing their use.